Health economic evaluations of interventions to increase physical activity and decrease sedentary behavior at the workplace: a systematic review - Nathanael Lutz; Peter Clarys; Irène Koenig; Tom Deliens; Jan Taeymans; Nick Verhaeghe (Nordic Association of Occupational Safety and Health (NOROSH), 2020)
OBJECTIVE: The workplace is an ideal setting to implement public health strategies, but economic justification for such interventions is needed. Therefore, we performed a critical appraisal and synthesis of health economic evaluations (HEE) of workplace interventions aiming to increase physical activity (PA) and/or decrease sedentary behavior (SB). METHODS: A comprehensive search filter was developed using appropriate guidelines, such as the Peer Review of Electronic Search Strategies (PRESS) checklist, and published search algorithms. Six databases and hand searches were used to identify eligible studies. Full HEE of workplace interventions targeting PA/SB were included. Methodological quality was assessed using the Consensus Health Economic Criteria (CHEC) list. Two researchers independently performed all procedures. Hedges' g was calculated to compare intervention effects. Outcomes from HEE were recalculated in 2017 euros and benefit-standardized. RESULTS: Eighteen HEE were identified that fulfilled on average 68% of the CHEC list criteria. Most studies showed improvements in PA/SB, but effects were small and thus, their relevance is questionable. Interventions were heterogeneous, no particular intervention type was found to be more effective. HEE were heterogeneous regarding methodological approaches and the selection of cost categories was inconsistent. Indirect costs were the main cost driver. In all studies, effects on costs were subject to substantial uncertainty. CONCLUSIONS: Due to small effects and uncertain impact on costs, the economic evidence of worksite PA/SB-interventions remains unclear. Future studies are needed to determine effective strategies. The HEE of such interventions should be developed using guidelines and validated measures for productivity costs. Additionally, studies should model the long-term costs and effects because of the long pay-back time of PA/SB interventions.